Can surgery be the last resort? A non surgical approach to temporo-mandibular joint disorders in children and adolescents: a review - Sagar, Mylavarapu Krishna; Tiwari, Priyanka; Tiwari, Priyanka; Lohiya, Juhi; Lohiya, Juhi; Shinde, Christopher Vinay; Shinde, Christopher Vinay; Jain, Suyog; Jain, Suyog (International Journal Of Community Medicine And Public Health, 2021)
Temporo-mandibular joint disorder, also known as temporo-mandibular disorder, or simply TMD is a major taxing condition for the children or the adolescent. It not only elicits physical pain and discomfort but also has a very deep psychological impact on the child. But is the surgical treatment any less frustrating and nerve wrecking? The answer is ruefully no. But yes, the entire treatment can be less traumatic to the patient. Here we put forward the various treatment options for TMDs besides surgery.